Preparation of Multiwall Carbon Nanotubes/Alumina Precursor Composites - Wang, Jing; Xu, Yong; Zhang, Mingxu (Asian Journal of Chemistry, 2012)
In this study, the multi-walled carbon nanotubes (MWCNTs) were modified with a mixture of concentrated HNO3/H2SO4 (3:1 by volume). The TEM showed that the modified MWCNTs were well dispersed. Compared with raw MWCNTs, the modified MWCNTs can disperse uniformly in a mixture of saturated aqueous solution of NH4HCO3, NH3·H2O and little sodium dodecyl benzene sulfonate (SDBS) solution. The TEM and XRD of the powders of composites indicated that the alumina precursor may wrap the MWCNTs absolutely.